The impact of eczema involving visible areas of the skin on patients' quality of life. Issue 2 (23rd April 2022) - Hang, Li; Saint Aroman, Marketa; Taieb, Charles; Baissac, Catherine; Merhand, Stephanie; Ortiz‐Brugués, Ariadna; Torrelo, Antonio
Abstract: Rational: Many studies have evaluated the impact of eczema according to the established severity. However, the specific impact of the location of eczema on the quality of life (QoL) has not been assessed. Objective: In the present study, we focus on the burden of disease caused by the involvement of atopic dermatitis (AD) on visible areas of the face and hands. Methodology: This study mobilized for each of the six countries where it was implemented (Canada, China, Italy, Spain, Germany and France), targeting a representative sample according to the quota method of their population aged 18 years and over. QoL was assessed through the QoL index (DLQI). Results: We identified 801 people who reported having suffered exclusively from AD in the past 12 months. Overall, 31.7% ( n = 257) of the population considered their skin disease to be embarrassing with consequences in their personal life. Regarding stigmata, 15.7% ( n = 126) of people with eczema felt rejected, 15.5% ( n = 124) felt they were looked at with disgust and 33.1% ( n = 265) expressed a sense of discouragement. A significant impact was observed in 31.5% ( n = 145) of patients who had visible damage versus 12.3% ( n = 42) of patients with no visible damage ( p < 0.0001). The difference was also significant ( p < 0.001) when the average DLQI was assessed (6.6 vs. 4.8). Discussion: The degradation of the QoL by AD is maximal when the hands and the face are affected simultaneously. The impact is also significantly higher when the hands are exclusively affected (compared to the face). The impact on the QoL is strongly linked to the experience and the lived experience of each patient, and the stigmata of the patients and their feelings of rejection are obvious. Surprisingly, exclusive hand involvement caused a higher impact in QoL than exclusive face involvement. Simultaneous involvement of the face and hands greatly amplifies the deterioration in QoL